Institutionalization of Dispute Boards as an Alternative Conflict Resolution Mechanism in Ecuador - Encalada Carrera, Gissella Michelle (Ius Humani. Jornal do direito, 2025)
This study focuses on presenting a comprehensive approach to Dispute Boards to understand the fundamental generalities and analyze several practical cases that have transcended, English-speaking borders and have become successful benchmarks in the application of this mechanism. This provides us with a more diverse international perspective for understanding its effectiveness in different contexts. In Latin America and in Spanish-speaking countries, the literature on this topic is limited, requiring research to strengthen its understanding to expand the bibliography and subsequently develop regulations. Therefore, this research is conducted to expand knowledge regarding an alternative justice resolution mechanism to traditional justice, which can be applied in projects that involve diverse areas and the participation of numerous stakeholders. An approach has been developed regarding Dispute Boards in Ecuador, with a regulatory breakdown and the presentation of two projects that are paradigmatic in the use of this ADR. This review will provide a better understanding of how this MASC has been managed to date in Ecuador and will assess whether the necessary tools exist for a possible future expansion of this MASC in regulatory frameworks.